Clinical trials of antibody drugs in the treatments of atopic dermatitis - Zhou, Guihao; Huang, Yueyao; Chu, Ming (Frontiers in Medicine, 2023)
Atopic dermatitis (AD) is one of the most common, relapsing, chronic inflammatory skin disease,be being regarded as a global healthy problemhealth issue. Recent studies have shown that Th2 cell-mediated type 2 immunity plays a central role in AD. The type 2 inflammatory cytokines such as IL-4, IL-13, IL-22, IL-31, IL-17 and IL-5 mediate the pathogenesis of AD. A variety of antibody drugs targeting these cytokines have been developed to treat AD in clinics. Notably, several antibody drugs have been approved by FDA, including Dupilumab and Omalizumab, which exhibit high efficacy in treating AD. have exhibited high efficacy in treating atopic dermatitis in previous studies, demonstrating that they could be therapeutic methods for AD patients. Herein, we reviewed the clinical trials of antibody drugs in the treatment of AD, which provides a useful guideline for clinicians to treat patients with moderate-to-severe AD in clinics.